Оптимізований метод вимірювання позитронних анігіляційних спектрів у наноматеріалах з розвиненою поруватістю для сенсорних застосувань - Клим, Галина; Костів, Юрій; Чалий, Дмитро; Івануса, Андрій; Ткачук, Тарас (Видавництво Львівської політехніки, 2016)
Запропоновано та використано оптимізований за апаратною складністю метод вимірювання позитронних анігіляційних спектрів для дослідження вологочутливої кераміки MgО-Al2O3 з розвиненою нанопоруватістю. Показано, що в разі розкладу спектрів на чотири компоненти вдається оцінити розміри нанопор за моделлю Тао-Ельдрупа та вивчити процеси, які відбуваються в них. Встановлено, що частка нанопор радіусом ~1,5 нм на порядок перевищує частку пор з радіусом ~ 0,3 нм, в яких також відбувається анігіляція ортопозитронію у адсорбованій воді. Предложен и использован оптимизированный за аппаратной сложностью метод измерения позитронных аннигиляционных спектров для исследования влагочувствительной керамики MgО-Al2O3 с развитой нанопористостью. Показано, что при разложении спектров на четыре компоненты удается оценить размеры нанопор по модели Тао-Ельдрупа и изучить процессы, происходящие в них. Установлено, что доля нанопор радиусом ~ 1,5 нм на порядок превышает долю пор с радиусом ~ 0,3 нм, в которых также происходит аннигиляция ортопозитрония в адсорбированной влаге. An optimized by hardware complexity method for measuring of positron annihilation lifetime spectra was proposed and used to investigation of humidity-sensitive MgO-Al2O3 ceramics with advanced nanoporosity. Positron-positronium annihilation spectrum were analyzed using four-component fitting procedures. It is shown that this technique can be used to investigation of nanopores transformation in humidity-sensitive MgO-Al2O3 ceramics as porosimetry method. It is shown that Tao-Eldrup model can be used for study of size of nanopores smaller then 1,5 nm. It has been shown that for MgO-Al2O3 ceramics two positron annihilation channels should be considered – the positron trapping with shortest t1 and middle t2 lifetimes and ortho-positronium decaying with the longest t3 and t4 lifetimes, these channels being independent ones. Assuming the two-state positron trapping model for spinel ceramics, four components in the fit of the experimental spectra can be associated with the microstructure peculiarities of the spinel. This microstructure exhibits characteristic octahedral and tetrahedral cation vacancies (t1, I1), positron trapping extended defects located near grain boundaries and positron traps in the free-volume entities (t2, I2). Ortho-positronium decay in nanopores of ceramics is described by t3, I3 and t4, I4. Within the formalism of this model, the open volume entities free of the electron density are treated as defects, while hypothetical structure without these entities is treated as the defect-free bulk. It is established that the third component of lifetime spectra gives information about ortho-positronium decaying in nanopores with water and fourth component reflects ortho-positronium trapping in free-water volume of nanopores. It is established that in inner structure ceramic materials there are two types of nanopores. The intensity of the third component of the spectrum increases in water-filled samples, while the intensity of four components – decreases. The most significant changes caused by water adsorption processes are observed in largest nanopores with radius of ~1,7 nm. Reducing the value of the lifetime t4 after drying of ceramics can be due to the formation of thin layers of water molecules surrounding the large pores. The lifetime t3 decreases after water vapor of ceramics with a gradual increase in drying and intensity I3 grows, indicating annihilation of ortho-positronium in water-filled nanopores. The presence of water in the nanopores of smaller radius of ~0.3 nm after drying reflects increasing of intensity I3 and a slight decreasing of lifetime t3. It is noted that ortho-positronium lifetime ~1,7 ns reflects the annihilation in the water “bubbles” with radius of ~0.3 nm.
Keywords: позитронна анігіляційна спектроскопія; метод дослідження структури; сенсорна кераміка; нанопори; адсорбція; позитронная аннигиляционная спектроскопия; метод исследования структуры; сенсорная керамика; нанопоры; адсорбция; positron annihilation lifetime spectroscopy; method to structural investigation; sensor ceramics; nanopores; adsorption; 620.179.1.05